TRANSCRIPTION FACTOR BRN-3α AND PROSTATE CANCER, RELATION WITH HORMONE RECEPTORS AND AKT/M-TOR SIGNALING PATHWAY ACTIVATION - L. V. Spirina; A. K. Gorbunov; I. V. Kondakova; E. M. Slonimskaya; E. A. Usynin (Сибирский онкологический журнал)
Introduction. The transcription factor Brn-3α (product of the POU4F1) plays a significant role in carcinogenesis. The purpose of the study was to investigate Brn-3α, AR, ERα expressions in tissues of benign prostatic hyperplasia and prostate cancer as well as to determine their association with AKT/mTOR signaling pathway activation.Material and methods. The study included 30 patients with locally advanced prostate cancer and 15 patients with benign prostatic hyperplasia. The expression levels of Brn-3α, AR, ERα and the components of AKT/m-TOR signaling pathway were determined using RT-PCR assay.Results. Overexpression of Brn-3α in prostate cancer tissues was found to be associated with high level of ERα mRNA. High expression of AR was revealed in tissues of benign prostatic hyperplasia and prostate cancer. High expression levels of AKT, m-TOR and PTEN were observed in prostate cancer tissues. However, no significant changes in PTEN mRNA level were found in tissues of prostatic hyperplasia. Conclusion. Brn-3α transcription factor was associated with prostate cancer and accompanied with high expression levels of ERα, AKT and m-TOR.